Principles and Practice of Geriatric Surgery - Rosenthal, Ronnie A.; Zenilman, Michael E.; Katlic, Mark R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This new edition builds upon the foundation of the first and second editions of the handbook, volumes separated by a decade of experience in the field, in a format that is both comprehensive and fluid. The combination of print and electronic versions will promote more rapid up-dating of chapters as new information appears. The Third Edition opens with general principles. The broad body of the volume encompasses diseases of the elderly and physiologic changes by system, as well as geriatric syndromes, perioperative management, and transitions of care into post-acute settings. The large concluding section is comprised of specialty-specific results of surgery in the elderly and suggested modifications recommended by experienced surgeons. Principles and Practice of Geriatric Surgery provides a comprehensive account that will allow all providers of healthcare to the elderly understand the issues involved in choosing surgery as a treatment option for their patients.
Section I: Principles -- Principles of Geriatric Surgery -- Defining Quality of Care -- Basic Science of Aging -- Surgery in Centenarians -- Section II: Pre-Operative Assessment and Perioperative Planning -- Patient Centered Surgical Decision -- Anesthesia Evaluation -- Geriatric Syndromes -- Frailty -- Function and Pre-habilitation -- Cognitive Function -- Nutrition -- Polypharmacy -- Cancer in Older Adults -- Diabetes in Older Adults -- Cardiac Disease in Older Adults -- Pulmonary Disease in the Older Adult -- Renal Disease in Older Adults -- Traumatic Injury in Older Adults -- Ethical Issues in Older Adults -- Legal Issues in Older Adults -- Section III: Peri-Operative Care -- Anesthetic Management -- Pain Management -- Post-Operative Delirium -- Models of Care -- Nursing Issues in Older Adult Surgery Patients -- Intensive Care in Older Adult Surgery Patients -- Wound Healing -- Enhanced Recovery After Surgery -- Section IV: Transitions of Care -- Transitioning Care of Discharge -- Rehabilitation and Functional Recovery -- Available Government and Community Resources -- Outcomes of Surgery in Older Adults -- Section V: Specific Specialties -- Neurosurgery -- Otolaryngology, Head and Neck Surgery -- Oral Surgery -- Breast Surgery -- Heart Surgery -- Vascular Surgery -- Lung Surgery -- Esophageal Surgery -- Stomach and Duodenal Surgery -- Large Bowel Surgery -- Anal Rectal Surgery -- Abdominal Wall and Hernia Surgery -- Liver and Biliary Tract Surgery -- Pancreatic Surgery -- Renal Surgery -- Baldder and Prostate Surgery -- Gynecologic Surgery -- Orthopedic Surgery -- Skin and Soft Tissue Surgery -- Transplantation Surgery.
Keywords: Surgery; Anesthesiology; Geriatrics; General Surgery; Anesthesiology; Geriatrics/Gerontology.